2018
DOI: 10.1007/s10943-018-0701-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Palliative Care Training on Last-Year Nursing Department Students’ Perception on Regarding Spirituality and Spiritual Care: A Single-Group Pretest–Posttest Intervention Study

Abstract: Spiritual care is a part of integrated care and should not be considered as a separate aspect of palliative care. Spirituality is seen as a requirement that must be met for all patients. The aim of this study is to determine the influence of palliative care on the perception levels of student nurses regarding spirituality and spiritual care. The research was carried out as a single-group pretest-posttest intervention study. The study was conducted with 70 student nurses. Data were collected via personal inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
0
17
0
3
Order By: Relevance
“…Spirituality can be expressed through various religious practices such as rituals and living by certain religious values. Even those who do not consider themselves as religious can have a spiritual dimension (Barber, 2019;Fowler, 2017;Koenig, George, & Titus, 2004;Özveren & Kirca, 2019). Researchers reported that the concept of religion and spirituality are different (Taliaferro, 2008) and that it is misleading when the term religion is synonymously used with spirituality (Lepherd, 2014;Sessanna, Finnell, & Jezewski, 2007).…”
Section: Spirituality and Religionmentioning
confidence: 99%
“…Spirituality can be expressed through various religious practices such as rituals and living by certain religious values. Even those who do not consider themselves as religious can have a spiritual dimension (Barber, 2019;Fowler, 2017;Koenig, George, & Titus, 2004;Özveren & Kirca, 2019). Researchers reported that the concept of religion and spirituality are different (Taliaferro, 2008) and that it is misleading when the term religion is synonymously used with spirituality (Lepherd, 2014;Sessanna, Finnell, & Jezewski, 2007).…”
Section: Spirituality and Religionmentioning
confidence: 99%
“…A study among PC nurses found that they perceive death as a natural and inevitable process and as their experience increases, they become desensitised [ 253 ]. A study showed that 55.7% of 70 nursing students had never heard of spiritual care [ 254 ]. Another study investigating the cultural mourning ritual, the ‘First Feast’, found this tradi tion helped to ease the grief response of relatives and might be a useful auxiliary method for PC teams to help grieving families [ 255 ].…”
Section: Resultsmentioning
confidence: 99%
“…The nurses’ pain management knowledge was positively correlated to the length of working experience in the oncology unit. Ozveren and Kirca [ 254 ] English Journal paper Cross-sectional To determine the influence of PC training on the perception levels of nurses regarding spiritual care. 55.7% of the nursing students stated that they had never heard of spiritual care, and 81.4% had not obtained any information regarding spiritual care.…”
Section: Supplementary Tablementioning
confidence: 99%
“…The profession of nursing is a very stressful occupation, and nurses are constantly exposed to trauma and stress. 19 Under this intense stress, it is very important for nurses to balance their positive and negative affectivities according to their environment and events they experience in terms of providing holistic care to their patients. In this study, it was found that the nurses' SSPS mean scores were generally (86.8%) high (Table 2).…”
Section: Discussionmentioning
confidence: 99%